A comparison of lutein, spray-dried Chlorella, and synthetic carotenoids effects on yolk colour, oxidative stability, and reproductive performance of laying hens - Englmaierová, M.; Skřivan, M.; Bubancová, I. (Czech Journal of Animal Science, 2013)
ISA Brown hens were fed diets supplemented with the synthetic carotenoids Carophyll Red and Carophyll Yellow at 20 and 15 mg/kg, respectively, lutein at 250 mg/kg, and the algae Chlorella at 12.5 g/kg. The synthetic carotenoids, lutein, and Chlorella significantly increased egg weight (P < 0.001), shell weight (P < 0.001), and thickness (P = 0.017) and decreased the yolk/albumen ratio (P = 0.035) of the eggs. Lutein but not the Carophylls or Chlorella significantly increased the shell breaking strength (P = 0.032). Furthermore, the carotenoids and Chlorella significantly (P < 0.001) increased yolk colour, and the yolk redness increased significantly (P < 0.001) in the following order: control < Chlorella < Carophyll < lutein. Lutein and Chlorella increased the yellowness of the yolks, and boiling the eggs for 5 min increased the redness of the yolks, while boiling them for 10 min increased the lightness and reduced the colour of the yolks. Supplementation of feed with lutein and Chlorella significantly (P < 0.001) increased the concentration of lutein (from 12.8 to 133.9 and 49.0 mg/kg dry matter) and zeaxanthin (from 9.2 to 123.9 and 40.1 mg/kg dry matter) in the yolks, and all carotenoids and Chlorella significantly (P < 0.001) increased the oxidative stability of the lipids of fresh eggs and eggs that had been stored at 18°C for 28 days.
Keywords: carophyll; alga; egg quality; yolk colour; cooking length